Comparison of Modular Control during Smash Shot between Advanced and Beginner Badminton Players - Naoto Matsunaga; Koji Kaneoka (Applied Bionics and Biomechanics)
This study investigated muscle synergy during smash shot in badminton and compared synergies of advanced players (more than 7 years experience) and beginner players (less than 3 years experience). The dominant hand of all players was the right side. Muscle activities were recorded on both sides of the rectus abdominis, external oblique (EO), internal oblique/transversus abdominis (IO/TrA), and erector spinae. Additionally, the right side of the biceps brachii, triceps brachii, flexor carpi radialis, flexor carpi ulnaris, and flexor digitorum profundus muscle activities were recorded. All data was obtained using surface electromyography. Synergy was extracted from electromyography signals using nonnegative matrix factorization. Extracted synergies in each group were compared using scalar product (SP) which is the similarity index. As a result, two synergies were extracted in the beginner players and three synergies were extracted in advanced players. Beginner and advanced players had one synergy in common (SP = 0.86) that was mainly on the left side of the EO. It activated in the early stroke and had a role of side bending from the left to hit the shuttlecock at a higher point. Another synergy that had coactivation of the IO/TrA and forearm muscles at impact was extracted only for advanced players and it may enhance the smash shot performance in badminton.